2021
DOI: 10.34117/bjdv7n4-574
|View full text |Cite
|
Sign up to set email alerts
|

Resistance profile of Staphylococcus sp. isolates from tilapia fillet samples Oreochromis niloticus from the northwestern region of Paraná state, Brazil / Perfil de resistência de Staphylococcus sp. isolados de amostras de filete de tilápia Oreochromis niloticus da região noroeste do estado do Paraná, Brasil

Abstract: Staphylococcus sp. are responsible for several clinical problems in fish farming and humans. This microorganism has a high risk associated with its presence in large numbers, as they have the ability to produce, under certain conditions, thermostable enterotoxins, which, when ingested, cause poisoning and various foodborne diseases. Present in aquaculture environments, Staphylococcus sp, have great potential to acquire antibiotic resistance, due to the use of such substances in the indiscriminate treatment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Most strains were resistant to erythromycin (54.54%) strains), followed by clindamycin (31.81%). Rosa et al (2021) found lower values for tilapia fillets, with 12% of strains resistant to erythromycin and 20% to clindamycin. However, in the analysis of antimicrobial susceptibility of bacteria isolated from Jundiá, Costa et al (2008) found a higher resistance to erythromycin (27.27%).…”
Section: Table 1 Mean Bacteriological Count Values Of Musselsmentioning
confidence: 87%
See 1 more Smart Citation
“…Most strains were resistant to erythromycin (54.54%) strains), followed by clindamycin (31.81%). Rosa et al (2021) found lower values for tilapia fillets, with 12% of strains resistant to erythromycin and 20% to clindamycin. However, in the analysis of antimicrobial susceptibility of bacteria isolated from Jundiá, Costa et al (2008) found a higher resistance to erythromycin (27.27%).…”
Section: Table 1 Mean Bacteriological Count Values Of Musselsmentioning
confidence: 87%
“…The most efficient antimicrobial was gentamicin, with only 4.54% of resistance and 86.36% of susceptibility. Rosa et al (2021) found slightly higher values for gentamicin, with 14% of resistant strains.…”
Section: Table 1 Mean Bacteriological Count Values Of Musselsmentioning
confidence: 88%
“…Tetracyclines have a broad spectrum bacteriostatic action, being used effectively in infections from both Gram-positive and Gram-negative bacteria. This class of antibiotics is widely found in the environment, especially in the soil, which may be related to the spread of antibiotic resistance (Da Rosa et al 2021;Zhang et al 2018).…”
Section: Virulence Factor and Antibiotic Resistancementioning
confidence: 99%